Problem-oriented computer simulators for solving theoretical and applied tasks of human physiology - Grygoryan, R.D. (PROBLEMS IN PROGRAMMING, 2018)
The goal of the paper is in overview of specialized mathematical models and computer simulators created for solving both applied and theoretical problems of human physiological systems. Examples of applied models aimed at optimizing of ways for increasing the resistance of a healthy person  to prolonged exposure to extreme loads of the environment (physical factors  of aerospace flight, as well as changed atmospheric pressure) are described. Along with models constructed within the framework of the traditional physiological paradigm of homeostasis, a model simulating the fight of organism’s different scale mechanisms against energy lack is described. This model is based on the author's concept of coexistence of cells of different specializations in a single organism. The general characteristic of the complex model and software simulator of the  organism-scale energy megasystem providing the fight of cells against energy deficit is given. The new physiological concept explained the endogenous mechanisms of circulation optimization and allowed the author to rethink the role of arterial pressure in the functioning of the body. Models of adaptive and pathological hypertrophy of the heart are briefly described. Software simulators are developed for IBM-compatible PC, programs are written in Borland Pascal for Delphi or in C++ for Visual Studio-10 environment.Problems in programming 2017; 3: 161-171